2007
DOI: 10.1007/s11738-007-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

Drought response of two bedding plants

Abstract: Bedding plants are an important part of the urban public space and private gardens. However, they are not always properly watered and suffer from drought stress, especially when grown in containers. In this trial a response to water stress of two commonly used species, impatiens (Impatiens walleriana Hook) and geranium (Pelargonium hortorum L. H. Bailey) were compared. The former is highly herbaceous and prone to wilting whereas the latter has hairy leaves and is better adapted to drought. Plants were grown at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 29 publications
4
41
0
1
Order By: Relevance
“…The effect of drought stress is usually greater on shoot growth than on root growth (Bacelar et al, 2007;Chyliński et al, 2007;Navarro et al, 2009). This behaviour is considered a criterion of plant adaptation to drought and could promote a more rapid establishment of ornamental plants in gardening or landscaping (Franco et al, 2006;2011).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of drought stress is usually greater on shoot growth than on root growth (Bacelar et al, 2007;Chyliński et al, 2007;Navarro et al, 2009). This behaviour is considered a criterion of plant adaptation to drought and could promote a more rapid establishment of ornamental plants in gardening or landscaping (Franco et al, 2006;2011).…”
Section: Discussionmentioning
confidence: 99%
“…data) presented the results from this study that had clearly demonstrated the roots to undergo large morphological and structural changes to ensure desirable distribution when adapting to terminal drought as described in wheat previously (Sharp and Davies 1985). These changes were (i) early reduction or check in root prolificacy in surface soils most likely due to the early death of ultimate branches, (ii) greater prolificacy of roots in soil depths below 30 cm, and to a much greater extent below 75 cm, thereby increasing the proportion of deeper soil roots (Lafitte et al 2001;Mishra et al 2001;Comas et al 2005;Benjamin and Nielsen 2006;Guswa 2008;Henry et al 2011), (iii) reduction in overall root biomass (Robertson et al 1980;Sánchez-Blanco et al 2002;dos Santos et al 2007;Navarro et al 2009;Álvarez et al 2009, 2011, (iv) reduction in root thickness, thereby increase in root length within the available root biomass, and to explore more volume of soil (Bañon et al 2003;Koike et al 2003;Kulkarni and Deshpande 2007;Chylinski et al 2007;Franco et al 2008;De Sousa and Lima 2010;Álvarez et al 2011;Wasson et al 2012;Bandyopadhyay 2014) and (v) early senescence of root system matching the shoot system senescence with no relevance to soil water availability. Similar pattern of RLD distribution was also observed in several legumes and cereal species such as field pea, rice, canola, cowpea, sunflower and sorghum (Liu et al 2011;Gowda et al 2012;Cutforth et al 2013;Moroke et al 2005).…”
Section: Adaptation To Terminal Droughtmentioning
confidence: 99%
“…Under water stress conditions, especially when coupled to excessive heat or radiation, chlorophyll is degraded (Havaux &Tardy, 1999), and the total content of this pigment in leaves can be an indicative of stress in plants (Gratani & Varone, 2004;Chylinski et al, 2007). In the present study, no reduction was verified in the total chlorophyll contents according to the water stress, which can be due to the fact that, especially at 25% of FC, most of the leaves dried without presenting chlorosis and the leaves used for analysis were still green.…”
Section: Resultsmentioning
confidence: 99%